(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Eye diseases lead to various vision impairments, and medical imaging techniques are crucial for accurate diagnosis and treatment of these conditions. This article provides a detailed overview of the types of medical images used for eye diseases, their working principles, advantages, and disadvantages. It also discusses specific imaging techniques for diseases such as retina, optic nerve, glaucoma, and cataract.